Adequacy Study on a Regional Airport to Achieve Energy Efficiency in a Renewable Form - da Rosa, Artur Rech; Villas-Boas, Valquíria (Scientia cum Industria, 2016)
Environmental sustainability is the use of the environment, giving it opportunity to regenerate, or finding ways to replace the environmental occupation by renewable means. In this context, the Caxias do Sul Regional Airport, which is a transport service provider to the Serra Gaucha region, can act as the concept of sustainable development, provided that there is the integration of environmental criteria in economic practice. In this context, photogeneration presents itself as an alternative to meet its energy demand making it sustainable from the point of view of this resource. In this paper, the airport demand for this type of energy, the PV plant design and analysis of economic viability are determined. The implementation of this system can save the airport 420,248.73 R$/year and it can generate the equivalent of R$ 235,653.74 / year in energy credits, being economically viable. This development, besides sustaining an image of green airport, can generate jobs for specialists in the field and can encourage and propagate the idea of using renewable energy. http://dx.doi.org/10.18226/23185279.v4iss1p21